HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN TEMPER TANTRUM PADA ANAK USIA TODDLER - Rahmawati, Eli (LPPM STIKES HUSADA JOMBANG, 2024)
Children are the most beautiful gift that steals the attention and affection of parents even when they are still in the womb. The Golden Age is a period when children will experience stimulation in all aspects of their development. Temper tantrums are an expression of anger in children which is shown in various ways such as screaming, crying, kicking, hitting, rolling around, or even throwing the body to the floor, which can even injure themselves or others. According to the Central Statistics Agency (BPS), the population of young children in Indonesia is estimated to reach 30.73 million in 2022. This study aims to synthesize articles that discuss the relationship between parenting patterns and the incidence of temper tantrums in toddler-aged children. This study uses a literature review method. Information was obtained from Google Scholar, pubmed and proquest with publications in national and international journals from 2018 to 2023. The article search method used PICOTS. Articles were selected using journal selection, selection using inclusion and exclusion criteria so that 4 journal articles were found. From the four journals, the results obtained were p value <0.005 for all journals. It was concluded that there was a relationship between parenting styles and the incidence of temper tantrums in preschool children.